2022
DOI: 10.21831/jk.v6i2.48290
|View full text |Cite
|
Sign up to set email alerts
|

Special education teacher’s need of alternative teaching materials for distance learning for students with special needs

Abstract: Teachers play an essential role in developing material for distance learning for students with special needs, fulfilling the practical principle, flexibility, the ability to accommodate the learning requirements, and the ability to ease students to understand the material through independent learning. However, many obstacles still hinder teachers in the execution. Through a survey of 115 special education teachers in the Special Region of Yogyakarta, this study is aimed at describing teachers' needs in develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…We found that the teachers were moderately anxious about distance learning during the COVID-19 pandemic, especially at the beginning. This result is consistent with the literature on techno-anxiety, emphasizing that, for teachers of students with Al Mulhim and Almulhem 10.3389/feduc.2024.1384925 Frontiers in Education 11 frontiersin.org special needs, integrating technology into teaching can induce anxiety (Betoncu and Ozdamli, 2019;Estrada-Muñoz et al, 2021;Fernández-Batanero et al, 2021;Potter, 2021;Ishartiwi et al, 2022;Nang et al, 2022;Rice, 2022;Zheng et al, 2022). This can lead to weakness in teaching students with special needs which affects students understanding of lessons.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We found that the teachers were moderately anxious about distance learning during the COVID-19 pandemic, especially at the beginning. This result is consistent with the literature on techno-anxiety, emphasizing that, for teachers of students with Al Mulhim and Almulhem 10.3389/feduc.2024.1384925 Frontiers in Education 11 frontiersin.org special needs, integrating technology into teaching can induce anxiety (Betoncu and Ozdamli, 2019;Estrada-Muñoz et al, 2021;Fernández-Batanero et al, 2021;Potter, 2021;Ishartiwi et al, 2022;Nang et al, 2022;Rice, 2022;Zheng et al, 2022). This can lead to weakness in teaching students with special needs which affects students understanding of lessons.…”
Section: Discussionsupporting
confidence: 87%
“…Potter (2021) claimed that introducing technology exacerbates special education teachers' struggles with stress, anxiety, and depression. In the context of special education teachers during the pandemic, techno-anxiety may have stemmed from several factors, including a lack of familiarity with or confidence in using digital platforms, a lack of support and training in the use of educational technologies, concerns about the effectiveness of technology in meeting the unique needs of their students, worries about technical glitches or connectivity issues during online instruction, the overall stress of adapting to a new teaching environment, and their need to keep up with the rapidly changing technological landscape (Betoncu and Ozdamli, 2019;Fernández-Batanero et al, 2021;Estrada-Muñoz et al, 2021;Ishartiwi et al, 2022;Nang et al, 2022;Rice, 2022;Zheng et al, 2022).…”
Section: Techno-anxiety Among Special Education Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Also self-regulation can help them to manage their work and life balance (Tiwa, Mandang, Kumaat, & Panambunan, 2022). In the other hand, teachers and parents can collaboration to optimize students' with autism success (Ishartiwi, Azizah, Handoyo, & Suseno, 2022). The research from Jackson and Hanlin (2020) showed increased students' ability after attending the learning using map concept, as proven by their correct answers to the science text-related questions.…”
Section: Discussionmentioning
confidence: 99%